Intermolecular interaction and cooperativity in an Fe(II) spin crossover molecular thin film system. (20th July 2022) - Hao, Guanhua; Dale, Ashley S; N'Diaye, Alpha T; Chopdekar, Rajesh V; Koch, Roland J; Jiang, Xuanyuan; Mellinger, Corbyn; Zhang, Jian; Cheng, Ruihua; Xu, Xiaoshan; Dowben, Peter A
Abstract: Compact domain features have been observed in spin crossover [Fe{H2 B(pz)2 }2 (bipy)] molecular thin film systems via soft x-ray absorption spectroscopy and photoemission electron microscopy. The domains are in a mixed spin state that on average corresponds to roughly 2/3 the high spin occupation of the pure high spin state. Monte Carlo simulations support the presence of intermolecular interactions that can be described in terms of an Ising model in which interactions beyond nearest-neighbors cannot be neglected. This suggests the presence of short-range order to permit interactions between molecules beyond nearest neighbor that contribute to the formation of largely high spin state domains structure. The formation of a spin state domain structure appears to be the result of extensive cooperative effects.